'Liver-first' approach for metastatic colorectal cancer. (April 2015) - Donati, Marcello; Stavrou, Gregor A; Stang, Axel; Basile, Francesco; Oldhafer, Karl J
ABSTRACT : The liver-first approach was proposed for the first time in 2006 to obtain resectability of stage IV colorectal cancer patients and complete the therapeutic plan. From then some groups have used this new revolutionary approach reporting promising results. Other alternative strategies have been proposed for metastatic patients. The authors reviewed the literature weighing the pros and cons of each strategy proposed to manage these advanced tumor stages. The therapeutic options are analyzed in the light of oncologic problems and evidence. Also problems, questions and perspectives are given. Even if the 'liver-first' approach seems to be a promising strategy, the ideal diagnostic–therapeutic flowchart for metastatic colorectal cancer is still difficult to standardize. The great heterogeneity of this population of patients is one of the main problems. A 'tailored approach' philosophy is necessary to calibrate, in a multidisciplinary setting, a case-by-case choice of therapeutic options.